Integrating Domestic Violence Education into the Pharmacy Curriculum - Harjit K. Khera; Rita Wardan; Hiu Tek Wu; Andy Ling; Suzanne M. Caliph (Pharmacy)
Domestic violence (DV) is a pervasive issue with significant implications for public health, yet it remains under-addressed in healthcare systems. Pharmacists, as accessible healthcare providers, are in a unique position to identify and support individuals affected by DV, but training in this area is often lacking in pharmacy education. This study explores the challenges of and opportunities for integrating DV education into the pharmacy curriculum by interviewing twelve pharmacy educators from Monash University. Using semi-structured interviews, data were analyzed thematically to identify key barriers and facilitators. The findings highlight several benefits of integrating DV education, including pharmacists’ accessibility to patients and their ability to play a vital role in recognizing and responding to DV. However, challenges such as time constraints, lack of confidence, insufficient training, and perceived limitations on pharmacists’ scope of practice were noted. Ethical and legal concerns regarding pharmacists’ roles in DV cases were also identified. This study concludes that integrating DV education into pharmacy curricula is essential; however, it requires significant barriers to be overcome, including the need for specialised training and collaboration with DV experts. This study recommends interdisciplinary workshops and greater faculty support to equip future pharmacists with the necessary skills to address DV effectively.